2018
DOI: 10.1111/tme.12504
|View full text |Cite
|
Sign up to set email alerts
|

Regional cerebral tissue oxygen saturation changes following blood transfusion in neuro‐intensive care unit patients – a pilot observational study

Abstract: RBC transfusion increased rSO significantly on both sides of the brain. As patients' outcomes were not studied, whether this increase in regional cerebral oxygen saturation is beneficial or if it is because of excess DO is still unclear. Further studies are required to clarify this issue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 27 publications
(27 reference statements)
0
5
0
Order By: Relevance
“…While we identified a number of studies evaluating alternative transfusion triggers such as ScVO2 [75][76][77][78], arteriovenous oxygen difference [79][80][81][82], cerebral oxygenation [82][83][84][85], tissue oxygenation, lactate [86][87][88][89][90], veno-arterial oxygen gradient [91,92], and mitochondrial oxygen [93], only one RCT [85] prospectively compared the use of physiologic transfusion triggers to traditional haemoglobin/haematocrit-based approaches. This RCT randomized patients to a "generic" algorithm or "patient-specific" algorithm involving measurement of cerebral oxygenation during cardiac surgery, of which transfusion was one component.…”
Section: Evidence Summarymentioning
confidence: 99%
“…While we identified a number of studies evaluating alternative transfusion triggers such as ScVO2 [75][76][77][78], arteriovenous oxygen difference [79][80][81][82], cerebral oxygenation [82][83][84][85], tissue oxygenation, lactate [86][87][88][89][90], veno-arterial oxygen gradient [91,92], and mitochondrial oxygen [93], only one RCT [85] prospectively compared the use of physiologic transfusion triggers to traditional haemoglobin/haematocrit-based approaches. This RCT randomized patients to a "generic" algorithm or "patient-specific" algorithm involving measurement of cerebral oxygenation during cardiac surgery, of which transfusion was one component.…”
Section: Evidence Summarymentioning
confidence: 99%
“…Several physiological factors have been shown to influence rScO 2 and V MCA including cardiac output, hemoglobin, and body temperature 25 . In this study, all the measurements were performed before surgery to eliminate the impact of surgical stimulation leading to cerebral hemodynamics changes.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have reported a decrease in c-rSO 2 with vasopressor infusion both in aSAH ( 48 ) and healthy patients ( 49 ), whereas it improved c-rSO2 values in the first few hours post-cardiac arrest ( 50 ). Studies reporting the effect of red blood cell transfusions in neurocritical care patients, a minority of which were aSAH, have also yielded conflicting results ( 51 53 ). Controlled hypercapnia, in the range of 50–60 mmHg, had some success to improve c-rSO 2 in two studies involving aSAH patients ( 22 , 54 ).…”
Section: Physiological Data—oxygenation Blood Flow Cerebrovascular Re...mentioning
confidence: 99%